Transcriptional response of two metallothionein genes (OcMT1 and OcMT2) and histological changes in Oxya chinensis (Orthoptera: Acridoidea) exposed to three trace metals. (November 2015) - Liu, Yaoming; Wu, Haihua; Yu, Zhitao; Guo, Yaping; Zhang, Jianzhen; Zhu, Kun Yan; Ma, Enbo
Highlights: Zn up-regulated OcMT1 and OcMT2 expressions in eight tissues of Oxya chinensis. Cd and Cu up-regulated OcMT1 and OcMT2 expressions in most of the tissues examined. Cd reduced the size and number of adipocytes in fat bodies of O. chinensis . Abstract: This study evaluated the transcriptional responses of two metallothionein (MT) genes ( OcMT1 and OcMT2 ) in various tissues (brain, optic lobe, Malpighian tubules, fat bodies, foregut, gastric caeca, midgut and hindgut) of Oxya chinensis (Thunberg) (Orthoptera: Acridoidea) after exposed to the trace metals cadmium (Cd), copper (Cu) and zinc (Zn) for 48 h. The study revealed that the exposure of O. chinensis to each of the three metals at the median lethal concentration (LC50 ) or lower concentration(s) up-regulated the transcriptions of both OcMT1 and OCMT2 in the eight tissues except for OcMT1 and OcMT2 with Cd in brain and gastric caeca, respectively, and OcMT2 with Cu in gastric caeca. These results suggested that the exposure of O. chinensis to the metals may enhance MT biosynthesis that protects tissues by binding these metals in various tissues. To examine possible histopathological effect of the metals, we examined the histological changes in the fat bodies after O. chinensis was exposed to each of these metals at LC50 . The exposure of Cd significantly reduced the size and number of adipocytes as compared with the control. However, such an effect was not observed in O. chinensis exposed to either Cu or Zn. These results suggested that fat bodies might be either significantly affected by Cd or play a crucial role in detoxification of excessive trace metals.